STRONG PHOTOLUMINESCENCE EMISSION AT ROOM TEMPERATURE OF ZnS MICROWIRES AND MICROBELTS GROWN BY THERMAL DEPOSITION - Nguyen Van, Nghia (VNU Journal of Science: Mathematics - Physics, 2017)
In this work, we report on the controlled synthesis of ZnS microstructures with high purity on Au-coated silicon substrates by thermal evaporation of ZnS powder in Ar gas ambient at atmospheric pressure. The growth mechanism is confirmed as a typical vapor–liquid–solid process. The prepared ZnS microstructures have wurtzite (hexagonal) structures. The catalytically grown ZnS microstructures, including microwires and microbelts, are tens of micrometers in length. EDS shows that the oxygen composition in the microstructures is trivial. The photoluminescence spectrum reveals strong ultraviolet emission and no other emission at room temperature also demonstrates that the ZnS microstructures are of high crystalline perfection. Optical transition from free exciton A, free exciton B are observed and analyzed through power-dependent at 10 K and temperature-dependent photoluminescence spectroscopy measurements performed from 10 to 300 K. Our results indicate that ZnS microstructures grown by thermal evaporation, suggesting a great promise for high-efficiency light-emitting devices and lasers in the UV region.